TYPE III CAWLEY ANDERSSON LESION IN A CASE OF ANKYLOSING SPONDYLITIS - Hegde, Deepak; Arjun, Ballal; C., Vinay Kumar; Rai, H. Ravindranath (Journal of Health and Allied Sciences NU, 2014)
Ankylosing spondylitis (AS) is a chronic inflammatory disease that affects especially males in the second and third decades of life.1The main clinical symptom is inflammatory back pain typically occurring at night and morning stiffness improving after exercise.1Apart from syndesmophytes and ankylosis of the spine resulting in rigidity, in longstanding ankylosing spondylitis, also focal destructive 1 discovertebral lesions (Andersson lesions) can occur.1The case we present here is of a 35 year old male patient who presented to us with the symptoms of pain of upper back and both shoulders for 6 years. Pain was followed with stiffness of the neck and shoulder. Radiography of the dorsolumbar spine revealed squaring of the vertebra, syndesmophytes, calcification of the anterior spinal ligament, end plate irregularity at D10-D11 level, ill defined sclerosis with fracture of the ankylosed spine, features consistent with Andersson lesion type III. He underwent posterior spinal fusion with good functional outcome.
Keywords: Andersson Lesion; Ankylosing Spondylitis; Cawley classification; Spinal fusion; Dorsolumbar spine